Peran Kurikulum Pendidikan Multikultural pada Pembelajaran Agama Islam - Sanuhung, Fitriyani; Nabila, Jihan; Wajdi, Muhammad Farid; Ningrum, Nur Rahma Setya; Agustina, Silfiya (ARZUSIN, 2021)
The curriculum with a multicultural approach has a very positive impact on the education system in Indonesia, which has many cultures. This curriculum is structured by looking at many differences so that this curriculum can be used by all students, not just one religion, ethnicity or race. Because a good curriculum is a curriculum designed with a multicultural system. This writing aims to determine the role of Islamic education curriculum development with a multicultural approach, using research methods, namely qualitative methods. The results of the research from the authors indicate that the multicultural education curriculum is a series and regulations regarding the content, objectives, and implementation processes of learning with a cultural approach that respects differences to achieve these educational goals.